Organised Crime: A Chaotic Notion - Beesley, Julie (2011)
Borrowed theories and principles from the physical sciences have enabled social scientists and criminologists to analyse well-worn theories and data from a new perspective. One such theory is chaos theory, a subset of the family of complexity theory, and an emerging perspective in postmodern criminology. Chaos theory is the science of non-linear and dynamic systems that appear random due to their complex behaviour, but in essence are deterministic and sensitive to initial conditions (popularly referred to as the butterfly effect). Chaos theory is best applied to systems that operate at local and global level, and that display signs of both order and disorder. Organised crime may be described as such a system. This paper explores the notion and attempts to analyse organised crime from a new perspective.Sydney Institute of Criminology; School of Social Sciences at the University of Western Sydne